The Determines of the Sticky Cost Behavior in the Jordanian Industrial Companies Listed in Amman Stock Market - Boraq Awad Magheed (STIE Malangkucecwara, 2016)
Traditionally costs are classiﬁed into ﬁxed, variable, and mixed cost according to the change in the level of activity. However, Anderson et al. (2003)/(ABJ) ﬁnd that the change in cost varies with a change in activities depending on the direction of change in revenue, and do not follow the traditional cost behavior model, this cost behavior is called sticky cost behavior. The objective of this study is to identify the impact characteristics of the firm on the degree of the cost stickiness of selling, general administration and advertisement cost (SG&A) and sold goods cost in the Jordanian indusnial companies listed in Amman stock market during 2000-20.13. AB] initial model is extended to acquire the firm characteristic variables, ordinary least squares (GL5) is us ed to run the regression. The result of the research support argument of AB], that the (SG&A) and sold goods cost in the Jordanian industrial companies listed on the Amman stock market follow the sticky costs behavior, and there is difference on the degree of cost stickiness between the ttype of cost used in the study, that is the cost of sold goods is less sticky than SG&A cost. In addition there are impacts of characteristics of the frm (assets density, employee’s density, debt density, and the proportion of ﬁxed assets) on the degree of cost stickiness in these companies. These impacts of characteristics of the frm differ according to the type of cost analysis.